Client-centered therapy with South Sotho clients at the South African police training college in Pretoria :|ban investigation into the emotion lexicon - Thulare, Serotele (University of Limpopo (Medunsa Campus), 2014)
Client-Centred therapy is a form of therapy that necessitates the use of emotion words in order to facilitate empathy between client and therapist. The current study investigated the availability of emotion words in the South Sotho language within the context of the South African Police Services. The availability of emotion words in the South Sotho language will help client-centred therapists to facilitate empathy with their South Sotho clients. The investigation in this study employed three phases. A convenient sample of South Sotho-speaking SAPS trainees participated in a free listing phase. The frequency of the words was recorded and the words with a frequency of 5 and above were retained. The list obtained from the free listing phase was given to a convenient sample of South Sotho language experts for prototypically rating. Cronbach’s Alpha was computed, and words with a mean of 0,4 and more were considered to be prototypes of the concept of emotion. Individual Client-Centered therapy was conducted with twelve SAPS members in English. The interviews were recorded, transcribed and given to two Client-Centered therapists to identify the emotion words. These words were compared with the words from phase two for their South Sotho translation. The findings indicate that almost 40% of the English emotion words from individual Client-Centered interviews did not have South Sotho equivalents. This implies that Client-Centered therapists will have difficulty facilitating empathy to their clients in South Sotho. And as such, the effectiveness of Client-Centered therapy will be compromised. However these results should be looked at with caution as the study’s sample was small and may not represent the larger population
Thesis (MSc (Clinical psychology)) -- University of Limppopo, 2011.
Keywords: Therapy.; Therapeutics